Exploring customer loyalty in the South African mobile telecommunications sector - Simon Morgan; Krishna Govender (Cogent Business & Management, 2017)
The South African mobile telecommunications environment has become increasingly competitive, thus there is increased focus on acquiring and retaining loyal customers in order to facilitate repeat purchases, guarantee future revenues and shield the customer base from competitive activity. In the light of the aforementioned, an online survey which comprised questions on loyalty, customer satisfaction, brand image, perceived quality and perceived value, was conducted among 110 customers of the South African (SA) mobile telecommunications industry. A number of hypotheses were formulated proposing relationships among the above-mentioned variables. The findings which resulted from structural equation and multiple regression modelling, revealed that customer satisfaction has the most significant positive effect on customer loyalty. Customer brand image and perceived value have a significant positive effect on customer satisfaction, but not customer loyalty. By implication, brand image and perceived value indirectly influence customer loyalty, through influencing customer satisfaction. The findings imply that the management of mobile telecommunications businesses in SA should focus on customer satisfaction and its antecedents, if they wish to develop a cadre of loyal customers.
Keywords: 650